PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DENGAN TEKNIK INDEX CARD MATCH UNTUK MENINGKATKAN HASİL BELAJAR KOGNITIF PESERTA DIDIK SMP PADA MATERI PENGUKURAN - Tampi, Munawwaroh; Irawan, Dedi; Azizahwati, Azizahwati (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
This study aims to describe the application of the think pair share learning model with the index card match technique to the cognitive learning outcomes of students and to find out the differences in student learning outcomes between those applying the think pair share learning model with the index card match technique and conventional learning models on measurement material. at SMPN 2 Pujud. The subjects in this study included class VII 1 and VII 2. Before being given treatment in the form of applying the think pair share learning model with the index card match technique, students were first given pretest questions and after being treated, students were given posttest questions. The research method used was quasi-experimental using nonequivalent control group design. The results of the descriptive analysis in the experimental class obtained an average absorption score of 62.9 with a standard deviation of 11.88 which is in the fairly effective category in terms of learning effectiveness. Meanwhile, the control class obtained an average absorption score of 52.8 with a standard deviation of 11.31, which is in the fairly effective category in terms of learning effectiveness.